Generation Z's Perception of Marriage Age Restrictions and Arranged Marriage Phenomenon - Mohamad Syafri; Riska Aulia Putri; Liannita Liannita; Siti Aisyah Humairah (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2022)
Indonesia has set rules for limiting the age of marriage for the community. However, it is still common for early marriage and matchmaking for children without involving children. This study wants to examine how young people, generation Z, see these two phenomena: the age limit for marriage and the phenomenon of child matchmaking. This research is survey research using a random sampling technique. The data was collected through an interview. The research’s sample is a group of people in the age range of 18-22 years who are in the city of Palu and its surroundings. The study results found that more than 75% of Generation Z supported the establishment of a marriage age limit. This is also consistent where more than 80% of Generation Z also tend to reject matchmaking without involving children. The conclusion of this study (1) Generation Z believes that marriage restriction rules can prevent early marriage, cope with mental health and psychological issues, and reduce the divorce rate and domestic abuse. (2) Generation Z tends to reject the matchmaking system without involving children because marriage is the children's right to have household harmony, and arranged marriage is outdated.